The Volunteer's Needs and Preparedness in Assisting Natural Disaster Victims - Nur Hafizah Md Akhir; Azlinda Azman; Noremy Md Akhir (Asian Social Work Journal, 2018)
This paper is discusses about volunteers’ needs in order to increase the preparedness in assisting natural disasters victims. Disasters are phenomenon that causes damage in properties and lives that limit individuals or societies’ abilities and well-being. Natural disasters such as landslides, tsunami, flood and typhoon happen almost every year. These natural disasters affect certain countries such as Japan, Indonesia, Thailand and Malaysia. The volunteers are the one who manage the humanitarian aids to the victims. The needs of the volunteers that been identified need to be evaluated in order to help to expedite the disaster relief management process. This is because the important aspects that need to be evaluated are planning, operational management and disaster training. Meanwhile, disaster preparedness represent as systematic planning in response to the disaster situation that needs to be done to those involved in disaster relief i.e volunteers. The concern on this aspect will help volunteer to be more active, positive and confident, in both physically and mentally when providing helps. Therefore, this concept paper will discusses volunteers’ needs in various perspectives and opinions in order to help in increasing the preparedness in assisting natural disasters victims, as well as increase the effectiveness throughout the relief process.